ChatGPT as a tool to develop students’ communicative competence in english - Nikitenko, Olga; Malyk, Yuliana (My University, 2024)
Learning in the age of digital technology has become many times easier and more accessible than ever before. With the help of advanced technology, individuals seeking to improve their language skills can now practice and engage with artificial intelligence (AI) coaches. It is common knowledge that he main goal of learning a foreign language is the formation of students’ communicative competence which means the development of skills and mastery of the language as a means of intercultural communication. These skills can be constantly developed and improved by using such a tool as ChatGPT.

Навчання в епоху цифрових технологій стало в рази легшим і доступнішим, ніж будь-коли раніше. Завдяки передовій технології люди, які прагнуть покращити свої мовні навички, тепер можуть практикувати та працювати з тренерами зі штучного інтелекту (AI). Загальновідомо, що основною метою вивчення іноземної мови є формування комунікативної компетенції учнів, що означає розвиток умінь і навичок володіння мовою як засобом міжкультурного спілкування. Ці навички можна постійно розвивати та вдосконалювати, використовуючи такий інструмент, як ChatGPT.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; students’ communicative competence; artificial intelligence; artificial intelligence; GPTchat; educational resources; комунікативна компетентність студентів; штучний інтелект; GPTчат; навчальні ресурси